Massive coagulopathy caused by the bite of a Crotalus basiliscus snake. Issue 1 (11th May 2017) - Meyer, Salome; Hartmann, Fabian; Stein, Philipp; Lenherr, Renato; Fuchs, Joan; Spahn, Donat R.
Summary: Crotalus basiliscus (Mexican West Coast Rattlesnake) is a crotalid snake native to Mexico. Whilst there is abundant information on bites by other pit vipers, there is none on the bite of this particular snake. We present the first case report of a bite by Crotalus basiliscus in a 57‐year‐old snake breeder, who after being bitten by one of his largest rattlesnakes, developed shock, a ventricular arrhythmia, profound coagulopathy and signs of compartment syndrome in his left lower extremity. Following repeated administration of antivenom, his clinical condition stabilised, but he required emergency coronary bypass surgery for newly diagnosed severe triple vessel disease.